Freedom of Expression - Tubić, Bojan (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
Freedom of expression, protected by Art. 10 of the European Convention on Human Rights, is a cornerstone of democratic society. It guarantees the right to hold opinions, and to receive and share information without interference from public authorities. However, this right is not absolute; restrictions are permitted when they are prescribed by law, pursue a legitimate aim, and are necessary in a democratic society.The European Court of Human Rights has developed extensive case law that balances freedom of expression with other rights and interests. In Handyside v. United Kingdom, the Court affirmed that freedom of expression protects not only agreeable ideas but also those that ‘offend, shock, or disturb’.Yet, limits have been upheld in cases involving hate speech or incitement to violence, such as Erbakan v. Turkey. The margin of appreciation doctrine allows states some discretion, although it is narrower when political or public-interest speech is involved, as seen in Lingens v. Austria.Overall, the jurisprudence of this court seeks to balance individual freedom with social responsibility. It continues to evolve in response to digital media, emphasizing that free expression remains vital to pluralism and democracy in Europe.Keywords: freedom of expression, restrictions, ECtHR